2011
DOI: 10.1590/s0100-40422011000600016
|View full text |Cite
|
Sign up to set email alerts
|

Formação de carbamato de etila em aguardentes recém-destiladas: proposta para seu controle

Abstract: Recebido em 1/10/10; aceito em 17/1/11; publicado na web em 29/3/11 ETHYL CARBAMATE FORMATION IN RECENTLY DISTILLED SUGAR CANE SPIRITS; PROPOSAL FOR ITS CONTROL. The commercial sugar cane spits redistillation decreased up to 92,5% their ethyl carbamate (EC) original content. Quantitative analysis of EC in 15 samples of sugar cane spirit (alembic and column), fresh distilled and collected in situ demonstrated that the urethane is formed mostly after distillation. The average time to achieve the complete EC form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
15

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 18 publications
1
21
0
15
Order By: Relevance
“…A possible explanation for the relationship of EC with the fermentation process was reported by Galinaro and Franco , who suggested that the cyanide ion is regarded as the main precursor in the formation of EC in spirits such as whiskey, cachaça and fruit distillates. The cyanide would be liberated from cyanogenic glycosides present in barley, cassava, oats, rye, wheat, apple, mango and rice, for example, when they are degraded enzymatically (or by heating during distillation).…”
Section: Resultsmentioning
confidence: 94%
“…A possible explanation for the relationship of EC with the fermentation process was reported by Galinaro and Franco , who suggested that the cyanide ion is regarded as the main precursor in the formation of EC in spirits such as whiskey, cachaça and fruit distillates. The cyanide would be liberated from cyanogenic glycosides present in barley, cassava, oats, rye, wheat, apple, mango and rice, for example, when they are degraded enzymatically (or by heating during distillation).…”
Section: Resultsmentioning
confidence: 94%
“…Foi sugerido anteriormente, 14,[18][19][20] que as cachaças destiladas em colunas de aço inox, em geral, apresentam concentrações de carbamato de etila superiores às das cachaças de alambique. A Tabela 1 apresenta teores de carbamato de etila para as três frações de alambique e do correspondente destilado de coluna, considerando-se em cada linha, o mesmo vinho.…”
Section: Resultsunclassified
“…Galinaro et al 20 demonstraram que durante a primeira semana após a destilação, ocorre um aumento gradual na concentração de carbamato de etila em aguardentes oriundas do mesmo vinho e destiladas em alambique e em coluna. Após este período, ocorre uma estabilização no teor de uretana.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A mean concentration of 317 µg L −1 ethyl carbamate was detected in 13 samples of commercial cachaça, and the samples presenting the lowest content of this compound (38–48 µg L −1 ) were double distilled . Also, redistillation reduced the ethyl carbamate content by up to 92.5% in 15 samples of commercial cachaça .…”
Section: Introductionmentioning
confidence: 97%